Kewirausahaan Mahasiswa Melalui Budidaya Burung Puyuh yang Diberi Ar Minum Mengandung Infusa Bunga Telang - Kusna Rinawati Zai; Anania Zega; Kristo Hotimanson Girsang; Iis Yuanita (Jurnal Pengabdian Kampus, 2025)
This Student Creativity Program (PKM) in Entrepreneurship aims to develop quail (Coturnix coturnix japonica) farming by supplementing drinking water with butterfly pea (Clitoria ternatea) infusion to produce functional eggs and carcasses. The planning stage was based on a literature review highlighting the potential of butterfly pea as a source of bioactive compounds such as anthocyanins, flavonoids, and antioxidants, which may improve immunity and enhance livestock production quality. The implementation included cage preparation, rearing of day-old quails until the laying phase, feeding management combined with butterfly pea infusion, daily egg collection, and the rearing of male and culled female quails for carcass production. The results showed an improvement in both productivity and egg quality, with an average daily production reaching 85.1% and average egg weight of 11.77 grams, which is higher compared to previous studies reporting 72.8% production and 10 grams egg weight. This innovation not only produces high-quality quail products but also provides functional food with added health benefits for consumers. Moreover, the activity had a positive impact on farmers by applying simple technology based on locally available herbal resources, thereby improving the competitiveness of quail products in the market.